Analisis Kemampuan Pemecahan Masalah Matematis Pada Materi Penjumlahan Dan Pengurangan di Kelas II SDN 1 Selojari - Fara Fatika Maharani; Putri Jenar Mahesa Ayu; Nur Kusuma Astuti; Diana Ermawati (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
Lower elementary school students usually have difficulty solving arithmetic puzzles. This is caused by variables inhibiting students, including lack of focus and low motivation to learn. This research was conducted to determine the proficiency of class II students at SD 1 Selojari in answering addition and subtraction questions through the use of narrative questions. The aim of the qualitative method of this research which uses a qualitative descriptive approach is to characterize mathematical problem solving abilities. The technique for selecting subjects in this research is using a purposive sampling technique, which is a technique for determining samples with various specific considerations using 11 class II students at SD 1 Selojari. The data collection techniques used were interview, observation and documentation methods. The data analysis technique uses data collection, data reduction, and drawing conclusions. The mathematical problem solving ability of second grade elementary school students in addition and subtraction material is quite high, namely 90%, as seen in the students' ability to work on the questions given and get high scores. The results of this research show that one in three students are still unable to solve problem questions and still need help.